Influencia de la calidad del servicio online en la satisfacción de los clientes Centennial y Millennial en los hoteles de 3 y 4 estrellas enfocado a los sitios webs - Chau Arroé, Alicia (2023)
The following study proposes the relationship between the quality of online service and customer satisfaction when using the website of 3- and 4-star hotels focused on the period of the COVID - 19 pandemic. In addition, to find the influence of the different dimensions that are formed in both variables and to know the impact that is generated for the consumer when starting with the process of acquiring the service through the website of the hotel. First, a research was carried out with the help of different bibliographies to identify the dimensions that form the quality of online service and customer satisfaction. Second, 29 questions were used to be asked by Centennials and Millennials using the survey technique. Third, to better analyze the results of the questionnaire, the correlation test between variables and simple linear regression was performed. In this way, measurable results could be obtained as a contribution to the proposal. As a conclusion, it can be said that there is a direct relationship between the dimensions that make up the quality of online service and customer satisfaction.